The development of a canine single-chain phage antibody library to isolate recombinant antibodies for use in translational cancer research - Lisowska, Małgorzata; Worrall, Erin G; Zavadil-Kokas, Filip; Charlton, Keith; Murray, Euan; Mohtar, M Aiman; Krejcir, Radovan; Hrabal, Vaclav; Brydon, Jack; Urionabarrenetxea, Ainhoa Gonzalez; Saliba, David G; Grima, Mariana; et al. (Cell reports methods, 2025)
The development of canine immunotolerant monoclonal antibodies can accelerate the invention of new medicines for both canine and human diseases. We develop a methodology to clone the naive, somatically mutated variable domain repertoire from canine B cell mRNA using 5'RACE PCR. A set of degenerate primers were then designed and used to clone variable domain genes into archival "holding" plasmid libraries. These archived variable domain genes were then combinatorially ligated to produce a scFv M13 phage library. Next-generation long-read and short-read DNA sequencing methodologies were developed to annotate features of the cloned library including CDR diversity and IGHV/IGKV/IGLV subfamily distribution. A synthetic immunoglobulin G was developed from this scFv library to the canine immune checkpoint receptor PD-1. This synthetic platform can be used to clone and annotate archived antibody variable domain genes for use in perpetuity in order to develop improved preclinical models for the treatment of complex human diseases.
Keywords: CP: cancer biology; psi; veterinary medicine; Peptide Library; rekombinantní proteiny; Dogs; monoklonální protilátky; Single-Chain Antibodies; next-generation sequencing; scfv phage libraries; Antibodies, Monoclonal; translational research; peptidová knihovna; Neoplasms; zvířata; Humans; nádory; translační biomedicínský výzkum; canine physiology; jednořetězcové protilátky; CP: immunology; Translational Research, Biomedical; lidé; Recombinant Proteins; Animals